DNA methylation pattern and restriction endonuclease accessibility in chromatin of a germ-line specific gene, the rainbow trout protamine gene. - Delcuve, G P (1987)
The chromatin structure of a germ-line specific gene, the TPG-3 gene, one of the rainbow trout protamine genes was analyzed in various tissues. The protamine genes are expressed in early stage testis but not in late stage testis, liver or erythrocyte. Five potential CpG methylation sites in the coding and flanking regions of the TPG-3 protamine gene were monitored in early and late stage testis, nucleoprotamine, liver and erythrocyte. In all cases the patterns of methylation were identical with only one CpG site at position -740 being methylated. Thus, the methylation pattern of this protamine gene remained the same independently of the expression of the gene. Two Msp I sites at positions -293 and/or -275 and +155 were accessible to the enzyme in the TPG-3 chromatin of early stage testis. Since the Msp I site at position -293 and/or -275 was also present in the TPG-3 chromatin of liver, only the site at position +155 within the transcribed region correlated with the expression of the protamine gene.